Novel regulators of airway epithelial barrier function during inflammation: potential targets for drug repurposing. (1st February 2022) - Sunil, Ahsan Anjoom; Skaria, Tom
ABSTRACT: Introduction: Endogenous inflammatory signaling molecules resulting from deregulated immune responses can impair airway epithelial barrier function and predispose individuals with airway inflammatory diseases to exacerbations and lung infections. Therapeutically targeting the specific endogenous factors disrupting the airway barrier therefore has the potential to prevent disease exacerbations without affecting the protective immune responses. Areas covered: Here, we review the endogenous factors and specific mechanisms disrupting airway epithelial barrier during inflammation and reflect on whether these factors can be specifically targeted by repurposing the existing drugs. Literature search was conducted using PubMed, drug database of US FDA and European Medicines Agency until and including September 2021. Expert opinion: IL-4 and IL-13 signaling are the major pathways disrupting the airway epithelial barrier during airway inflammation. However, blocking IL-4/IL-13 signaling may adversely affect protective immune responses and increase susceptibility of host to infections. An alternate approach to modulate airway epithelial barrier function involves therapeutically targeting specific downstream component of IL-4/IL-13 signaling or different inflammatory mediators responsible for regulation of airway epithelial barrier. Airway epithelium-targeted therapy using inhibitors of HDAC, HSP90, MIF, mTOR, IL-17A and VEGF may be a potential strategy to prevent airway epithelial barrier dysfunction in airway inflammatory diseases.